Mechanism of leukemogenesis induced by mink cell focus-forming murine leukemia viruses. - Li, J P (1991)
The Friend or Moloney mink cell focus-forming (MCF) virus encodes a recombinant-type envelope glycoprotein, gp70, that is closely related to the membrane glycoprotein, gp55, of Friend spleen focus-forming virus (SFFV). We have shown previously that gp55 has the ability to activate cell growth by binding to the cellular receptor for erythropoietin. Here we show that gp70 encoded by either the Friend or Moloney MCF virus also binds to the erythropoietin receptor and that coexpression of the receptor and gp70 in an interleukin-3 (IL-3)-dependent cell line can activate IL-3-independent growth. Furthermore, when the cDNA for the human IL-2 receptor beta chain, which is related by sequence to the erythropoietin receptor, was introduced into this cell line, it became growth factor independent after infection either with SFFV or with one of the two MCF viruses but not with an ecotropic virus. Based on these observations, we propose a mechanism for the early stage of leukemogenesis induced by the MCF-type murine leukemia viruses.